Big George Foreman [videorecording (DVD)] - Tillman, George, 1969-; Baldwin, Frank (Screenwriter); Gordon, Dan, 1947-; Davis, Khris; Mathews, Jasmine; Jones, Sullivan (Narrator); Gilliard, Larry; Magaro, John, 1983-; Trammell, Sam, 1971-; Sohn, Sonja; Whitaker, Forest (Sony Pictures Home Entertainment, 2023)
George Foreman makes a name for himself by channeling his childhood anger in the boxing ring, but when he has a near-death experience, he gives it all up to become a preacher.